Ecological Justice and Energy Transition Policy in Indonesia - Qurbani, Indah Dwi; Rafiqi, Ilham Dwi (Postgraduate School of Universitas Brawijaya, 2025)
The energy transition has been perceived as an urgent agenda, as the phenomena of climate change and environmental damage are increasing. Various arrangements and endeavors have been undertaken by many countries, including Indonesia, to overcome this challenge. One of these efforts is the formulation of a national energy transition policy. This paper aimed to examine policy directions and analyze gaps in the energy transition policy issues in Indonesia, as well as their relationship to ecological justice. The research method employed was a combination of normative legal research, statutory analysis, conceptual analysis, and historical analysis. The findings showed that (1) the direction of the national energy transition policy aimed at overcoming the impacts of climate change and environmental damage through the use and utilization of new and renewable energy (NRE). Various types of policies have been established, ranging from those related to bills to government regulations and those of the Minister of Energy and Mineral Resources. However, such policies had a dual orientation, which contained substance problems and overlapping arrangements. (2) The problems of the national energy transition policy would affect the fulfillment of access to justice, especially ecological justice. The transition from fossil energy to renewable energy could have a positive impact if the policy and implementation of exploring, exploiting, using, and utilizing renewable energy were truly oriented towards protecting and preserving the environment and social welfare. One indicator of the success of the national energy transition was the fulfillment of access to ecological justice as mandated by the Indonesian constitution.Keywords: Policy, Ecological Justice, Energy Transition in Indonesia, Introduction